International organisations in vocational education and training : a literature review - Klassen, Johannes [Verfasser] (My University, 2024)
„Although international organisations (IOs) are recognised as important actors in education, their involvement in vocational education and training (VET) remains underexamined. This article reviews the current state of research on IOs in VET, focusing on the ILO, OECD, UNESCO, and the World Bank, through an integrative literature review of 174 publications. The analysis identifies three roles attributed to IOs, highlighting crucial research gaps for future investigation. First, IOs are seen as important knowledge producers on VET, demonstrated by the implicit use of IO data in academic research. However, literature that explicitly analyses how IOs produce VET knowledge is largely missing. Second, IOs are described as organisations capable of formulating specific VET agendas. While there has been a particular interest in the World Bank’s views on VET, research that analyses and compares how other IOs develop their ideas on VET remains rare. Third, IOs are recognised as actors of VET policy transfer. Although existing research highlights the complexity of international and local factors in IOs’ attempts to influence national VET policies, more comparative case studies are needed to analyse concrete IO engagements. Addressing these gaps would contribute to a research agenda that takes into account the multifaceted agency of IOs in VET.“ (author’s abstract; BIBB-Doku)
Keywords: I 1.5 Internationale Organisationen & Institutionen; I 1 Internationale Berufsbildung; 370; Berufsbildung; Internationale Organisation; Berufsbildungsforschung; Berufsbildungspolitik; ILO; OECD; UNESCO; Weltbank; Literaturanalyse